On a class of problems on unsteady flow of viscous-plastic fluids in pipe-line - Chi, Nguyen Huu; Quang, Vu Duy; Thanh, Pham Hoai (Vietnam Journal of Mechanics, 1995)
Combining the quasi-stationary principle with velocity profile properties of respective steady flow and Sliozkin-Targ's approximation we introduce a method to solve a class of problems on unsteady flow of viscous-plastic fluid in pipe-lines. Using this method we solve the problems on unsteady pressure flow in the horizontal cylindrical tube. We also compare the obtained results with those of Tiabin showed in [1].